Principal’s Leadership Strategy to Improve the Competence of Educational Staff and School Facilities and Infrastructure at SMPN 2 Cigedug - Iman Romansyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The principal as a manager must have a strategy in developing educational infrastructure and improving the competence of education personnel, because one of the easiest indicators to measure to determine whether a school is of quality or not, can be seen from the completeness of educational facilities and infrastructure in supporting the learning process at school. This study aims to describe school leadership strategies in improving the competence of education personnel and school infrastructure at SMPN 2 Cigedug. This research uses a qualitative type of research with a case study approach. The object of this research was carried out at SMPN 2 Cigedug. Data collection techniques use observation, interviews, and documentation. The triangulation used to test the validity of the data is source triangulation. The results of this study include: 1) implementation of principals' leadership strategies including: a) providing training to staff or teachers on management of facilities and infrastructure within schools or in other institutions, b) increase awareness of school residents regarding the importance of the existence of facilities and infrastructure through guidance, counseling, and other activities, c) procure facilities and infrastructure in accordance with school needs and carry out repairs and maintenance of school-owned facilities and infrastructure. 2) Inhibiting and supporting factors in the implementation of the principal's leadership strategy are the inhibiting factors: a) lack of workshops and training from the government, b) lack of qualified S1 education personnel, c) difficult to reach school locations, d) inadequate facilities such as libraries and laboratories. As for the supporting factors: a) education personnel who are still willing to learn, b) providing motivation and support from the principal, c) the existence of salary guarantees from the local government for education personnel, d) providing opportunities for education personnel to attend training, e) improving the welfare of education personnel through special school programs.